Study protocol: a randomised controlled trial of supervised resistance training versus aerobic training in Sri Lankan adults with type 2 diabetes mellitus: SL-DART study - C. Ranasinghe; A. P. Hills; G. R. Constantine; G. Finlayson; P. Katulanda; N. A. King (BMC, 2018)
Abstract Background The prevalence of type 2 diabetes mellitus (T2DM) and cardiovascular diseases (CVD) is rising globally. T2DM is particularly problematic in South Asia with an estimated 10-15% of Sri Lankans diagnosed with the disease. Exercise is known to improve blood glucose, lipid profiles, blood pressure and adiposity, key goals in the management of T2DM. However, much of the evidence to date has been gained from white Caucasians who have a different body composition and disease profile compared to South Asians. Similarly, the recreational exercise culture is new to Sri Lankans and the effects of exercise on T2DM has not been studied in this population. Methods The Sri Lanka Diabetes Aerobic and Resistance Training (SL-DART) Study will be comprised of 2 components. Component 1 is a 12-week randomized controlled trial (RCT) to compare the effects of a supervised progressive resistance exercise program (RT) and aerobic exercise program (AT) with standard treatment/control (CN). Sedentary Sri Lankan adults with T2DM (aged 35-65 years) and with no contraindications to exercise will be randomized into one of 3 groups (AT, RT, CN). Exercise sessions will be conducted 2 days/week for 3 months. Baseline and post-intervention biochemical (glycemic control, lipid and liver profiles, inflammatory markers), anthropometric (height, weight, body circumferences), body composition, physical fitness, food preference (liking and wanting food) and quality of life parameters will be measured and compared between groups. Component 2 will be a qualitative study conducted immediately post-intervention via in-depth interviews to assess the barriers and facilitators for adherence to each exercise program. Discussion SL-DART Study represents one of the first adequately powered methodologically sound RCTs conducted in South Asia to assess the effects of resistance and aerobic exercise in participants with T2DM. Triangulation of quantitative and qualitative outcomes will enable the design of a culturally appropriate therapeutic physical activity intervention for Sri Lankans with T2DM, and the initiation of a professionally driven and specialized clinical exercise prescription service. Trial registration Sri Lanka Clinical Trials Registry; SLCTR/2016/017 . Date registered 17.06.2016. Universal trial number U1111-1181-7561.